Controlled Growth of Bilayer‐MoS2 Films and MoS2‐Based Field‐Effect Transistor (FET) Performance Optimization. (14th March 2018) - Fang, Mingxu; Wang, Fang; Han, Yemei; Feng, Yulin; Ren, Tianling; Li, Yue; Tang, Dengxuan; Song, Zhitang; Zhang, Kailiang
Abstract: The effect of hydrogen flow on MoS2 film synthesis via chemical vapor deposition is studied systematically. Large‐sized monolayer‐ and bilayer‐MoS2 triangles can be synthesized controllably at given temperatures. Optical microscopy, Raman spectroscopy, photoluminescence spectroscopy, and atomic force microscopy are used to characterize the number of layers, purity, and uniformity of the MoS2 triangle films. Moreover, the back‐gated field‐effect transistors (FETs) based on the monolayer‐ and bilayer‐MoS2 channels are fabricated using traditional micro‐nanoprocessing technology. Electrical behaviors are investigated and the bilayer‐MoS2 FETs show preferable performance with high mobility (≈21 cm 2 V −1 s −1 ), on‐current (≈22 µA µm −1 ), and a small degradation in the on/off ratio (1.1 × 10 7 ). Finally, the semiconductive phase MoS2 (2H‐MoS2 ) is transformed to a metallic phase (1T‐MoS2 ) to reduce the resistance in metal‐MoS2 contact. The FET device with 1T‐MoS2 contact enhances mobility (≈45 cm 2 V −1 s −1 ) and on‐current (≈50 µA µm −1 ) compared with the 2H‐MoS2 FETs. This work sheds light on the synthesis of variable‐layer MoS2 films and paves the way for further development regarding MoS2 film‐based devices. Abstract : The controlled synthesis of mono‐ and bilayer‐MoS2 is achieved by a specific H2 flow rate. Furthermore, phase transform engineering improves the contact between MoS2 and metal electrodes to optimize electrical transmission characteristics.By optimizing layers and contact, a high mobility( 45 cm 2 V –1 s –1 ) and on‐current (50 μA μm –1 ) can be achieved which greatly boost the application of 2D‐MoS2 in electrical fields.